Faktor Pengaruh Interaksi Aktif dalam Komunitas Online yang Disponsori Merek - Dian Ika Fitriani; Diah Priharsari; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Branded online communities are created by brands themselves in order to create a medium for marketing their products through interaction with brand enthusiasts. Unfortunately, not all brands can create an active online community that interacts, which can provide output for branding and brand sales. Researchers try to learn what factors influence the formation of a lively and active online community. The research was conducted by collecting data from the online community in the form of online text from the comments column. From the online text data, data analysis was then carried out using the literature driven coding method. Where this method refers to the coding process using a model framework obtained from two theories, namely Self Determination Theory and Self Disclosure Theory. The findings show that the five factors in the model framework, namely Relevance, Autonomy, Competence, Familiarity, and Valence, have a significant influence on the success of active interactions in branded online communities. The second finding, the researcher describes the presentation of the emergence of each factor and the factors obtained that have a dominant influence are Relationship by 25%, Competence by 22%, and Familiarity by 20%. The third factor shows the percentage of occurrences above the average. Through the results of this study, it is hoped that it can provide new perspectives and references in managing an online community for SMEs that are still developing.